Echinoderes xiphophorus sp. nov. – the first deep-water representative of Echinoderidae in the Sea of Japan (Kinorhyncha: Cyclorhagida) - Adrianov, Andrey V.; Maiorova, Anastassya S. (European Journal of Taxonomy, 2021)
A new species of echinoderid kinorhynchs, Echinoderes xiphophorus sp. nov. collected from oxidized brown silt at the deepest depression in the Sea of Japan, North-West Pacific, is described and illustrated using light and electron microscopy. This new representative of the most speciose kinorhynch genus is characterized by the unique set of spines and tubes and can easily be distinguished from most of its congeners. The second trunk segment bears three pairs of tubes in subdorsal, midlateral and ventrolateral position in both sexes; one pair of tubes on trunk segment 5 in lateroventral position and on trunk segment 8 in sublateral position; aciculate lateroventral spines on trunk segments 6–9; aciculate middorsal spines on trunk segments 4, 6, 8. This species is well recognized by very long tergal extensions of the posteriormost segment, some of the longest within the family Echinoderidae. Males of Echinoderes xiphophorus sp. nov. are well distinguished from all the congeners by extremely long sword-like appendages dorsally to three pairs of penile spines. The species constitutes the first deep-sea representative of the Echinoderidae in the Sea of Japan and the deepest representative of the Kinorhyncha in this sea.